A comparison of McGrath MAC, AIRWAY SCOPE®, and AceScope® video laryngoscopes in novice healthcare providers: a randomized crossover simulation study - Musashi Yahagi; Kyuma Omi; Yuichi Yaguchi (BMC Anesthesiology)
Abstract Background Video laryngoscopes are widely used for tracheal intubation, particularly in challenging airway scenarios. The McGrath MAC, AIRWAY SCOPE®, and AceScope® are popular video laryngoscopes with different design features. This study aimed to compare the effectiveness and usability of these three devices in novice healthcare providers during simulated tracheal intubation scenarios employing a manikin. Methods Sixty novice healthcare providers, including nurses and pharmacists, were enrolled in this randomized crossover study. Participants performed tracheal intubation using the McGrath MAC, AIRWAY SCOPE, and AceScope in both normal airway and cervical spine immobilization models. Primary outcomes were intubation success rate and time to intubation. Secondary outcomes included user preferences, device ease of use, and the incidence of dental injuries. Results The AIRWAY SCOPE demonstrated the shortest intubation time in both normal airway and cervical spine immobilization models (14.90 ± 1.76 s and 23.80 ± 2.43 s, respectively), followed by the McGrath MAC and AceScope. All devices exhibited high success rates, and there were no significant differences in perceived difficulty among the three video laryngoscopes. The incidence of dental injuries was generally comparable among the devices. However, in the cervical spine immobilization model, the AceScope demonstrated a significantly higher rate of dental injuries compared to the McGrath MAC (p < 0.05), highlighting a potential concern for clinical practice. Conclusions The AIRWAY SCOPE was the most efficient video laryngoscope in terms of intubation time, followed by the McGrath MAC and AceScope. However, all devices showed high success rates and no significant differences in perceived difficulty. Further research is needed to validate these findings in clinical settings and investigate the impact of device-specific features on intubation outcomes and dental injury incidence. Trial registration Registration number: jRCT1030240598 ( https://jrct.niph.go.jp/re/reports/detail/91422 ) The registration date of the clinical trial is January 8, 2025.UMIN000050394.